The first microbiological contamination assessment by deep-sea drilling and coring by the D/V Chikyu at the Iheya North hydrothermal field in the Mid-Okinawa Trough (IODP Expedition 331) - Yanagawa, Katsunori; Nunoura, Takuro; McAllister, Sean; Hirai, Miho; Breuker, Anja; Brandt, Leah; House, Christopher; Moyer, Craig L.; Birrien, Jean-Louis; Aoike, Kan; Sunamura, Michinari; Urabe, Tetsuro; et al. (Frontiers in Microbiology, 2013)
During the Integrated Ocean Drilling Program (IODP) Expedition 331 at the Iheya North hydrothermal system in the Mid-Okinawa Trough by the D/V Chikyu, we conducted microbiological contamination tests of the drilling and coring operations. The contamination from the drilling mud fluids was assessed using both perfluorocarbon tracers (PFT) and fluorescent microsphere beads. PFT infiltration was detected from the periphery of almost all whole round cores. By contrast, fluorescent microspheres were not detected in hydrothermally active core samples, possibly due to thermal decomposition of the microspheres under high-temperature conditions. Microbial contamination from drilling mud fluids to the core interior subsamples was further characterized by molecular-based evaluation. The microbial 16S rRNA gene phylotype compositions in the drilling mud fluids were mainly composed of sequences of Beta- and Gammaproteobacteria, and Bacteroidetes and not archaeal sequences. The phylotypes that displayed more than 97% similarity to the sequences obtained from the drilling mud fluids were defined as possible contaminants in this study and were detected as minor components of the bacterial phylotype compositions in 13 of 37 core samples. The degree of microbiological contamination was consistent with that determined by the PFT and/or microsphere assessments. This study suggests a constructive approach for evaluation and eliminating microbial contamination during riser-less drilling and coring operations by the D/V Chikyu.